Modelling Malaysian Mortality Improvement Using a Hybrid Logistic Spline - Nur Idayu Ah Khaliludin; Norrlaili Shapiee; Zarina Mohd Khalid; Siti Rohani Mohd Nor; Nurliyana Nurliyana Juhan; Rose Irnawaty Ibrahim; Yumn Suhaylah Yusoff (Penerbit UTM Press, 2026)
Indexed by WOS / MYCITE